PEMBINAAN ADMINISTRASI PEMERINTAHAN DESA OLEH CAMAT BELIMBING DI KABUPATEN MUARA ENIM, SUMATERA SELATAN - Dian Novita Fajar Sari (STIA Bengkulu, 2024)
The sub-district government is a level of government that has an important role in implementing services to the community, this then makes the sub-district head the spearhead in implementing general government tasks as well as some autonomous matters delegated by the Regent/Mayor to be implemented within the sub-district area. From the background above, the author found the main problems including: First, how is village government administration developed by the Belimbing subdistrict head in Muara Enim Regency? Second, what are the obstacles to village government administration development by the Belimbing subdistrict head in Muara Enim Regency. The research used is qualitative research. From the research results, development by the sub-district head of village government officials in a sub-district is needed to achieve orderly village government administration and an effective government system. This is based on the indicators used in this research, namely; Planning has been carried out optimally, guidance has been. However, it has not yet run optimally, the briefing has been carried out. Obstacles faced by the Belimbing sub-district government are implemented inadequate human resources owned by village officials and capabilities that do not match expertise in their field of work and the village government's delay in submitting accountability reports to the sub-district.